Prevalência de esofagite eosinofílica nos pacientes pediátricos submetidos a endoscopia digestiva alta - Gonçalves, Lara de Oliveira (2017)
Introduction: Eosinophilic esophagitis is a disease of recent recognition and its prevalence has increased exponentially in recent years, emerging as one of the most important esophageal diseases. It is defined as a chronic, immuno-mediated disease characterized clinically by signs of esophageal dysfunction and histologically by predominantly eosinophilic inflammatory infiltrate. In Brazil, esophageal eosinophilic diseases have no known incidence and prevalence. Objectives: To verify the prevalence of eosinophilic esophagitis (EoE) and proton-pump inhibitor-responsive esophageal eosinophilia (PPI-REE)in pediatric patients submitted to upper gastrointestinal endoscopy, with analysis of epidemiological data regarding sex, age, symptomatology, frequency of atopy, endoscopic and histological findings. Methods: A retrospective, observational and analytical study was carried out, with an evaluation of medical records of pediatrics patients aged 0 to 14 years submitted to upper gastrointestinal endoscopy in a tertiary hospital from January 2004 to January 2014. Results: A total of 4.071 upper digestive endoscopies were performed in 2.651 patients, considering the population of 253.706 children in the area of coverage. Seventy patients had esophageal biopsy with 15 or more eosinophils per large increase field, and 31 patients fulfilled diagnostic criteria for EoE, 13 for PPI-REE and 3 for eosinophilic gastroenteritis. There was no statistically significant difference between patients with EoE and PPI-REE in relation to age, gender, presence of atopy, symptomatology and endoscopic findings. The prevalence of confirmed eosinophilic esophagitis was calculated considering 0 to 14 years old local population, reached 1.22 children in each group of 10,000, while the prevalence of confirmed reached 0.51 / 10,000. Conclusion: The prevalence of EoE found in the study were similar to previously reported in literature and probably is underestimated due the difficult assess to upper digestive endoscopy. The increase awareness and suspicion around EoE leads to a necessity of adequate infrastructure to offer upper digestive endoscopy to perform the correct diagnosis of EoE.